2012
DOI: 10.4103/1319-3767.91733
|View full text |Cite
|
Sign up to set email alerts
|

Serologic markers of gluten sensitivity in a healthy population from the western region of Saudi Arabia

Abstract: Background/Aim:To identify the prevalence of gluten sensitivity in a healthy adult Saudi population within a low endemic area of celiac disease using IgA tissue transglutaminase antibody. The study was conducted as a prospective pilot study for Saudi attendees of a blood donation centre at King Faisal Specialist Hospital & Research Centre in Jeddah, Saudi Arabia.Patients and Methods:Individuals were invited to participate in the study and screened for gluten sensitivity using immunoglobulin A tissue transgluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…[16][17][18]29,30,36,38,39,42 Similarly, of 29 423 children screened in six studies, 133 children were reported to have CD. 17,[31][32][33][34][35]37,43 Therefore, the pooled prevalence of CD amongst children from Asian countries was 0.5% (95% CI 0.3%, 0.7%). 17,[31][32][33][34][35]37,43 There was no significant difference in the prevalence of CD amongst Asian children and Asian adults (P = 0.65).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…[16][17][18]29,30,36,38,39,42 Similarly, of 29 423 children screened in six studies, 133 children were reported to have CD. 17,[31][32][33][34][35]37,43 Therefore, the pooled prevalence of CD amongst children from Asian countries was 0.5% (95% CI 0.3%, 0.7%). 17,[31][32][33][34][35]37,43 There was no significant difference in the prevalence of CD amongst Asian children and Asian adults (P = 0.65).…”
Section: Resultsmentioning
confidence: 97%
“…17,[31][32][33][34][35]37,43 Therefore, the pooled prevalence of CD amongst children from Asian countries was 0.5% (95% CI 0.3%, 0.7%). 17,[31][32][33][34][35]37,43 There was no significant difference in the prevalence of CD amongst Asian children and Asian adults (P = 0.65). The I 2 test for heterogeneity in children and adult groups were 61% and 59%, respectively, and thus, age of the subjects could not explain the heterogeneity observed in the overall prevalence of CD in these studies.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Laboratories are often reliant on manufacturer's data for reference values (RVs); or commonly, reference data are generated from blood donors who inherently are more likely to be male and younger than seen in the general population. 11,12,21 We take advantage of access to the Busselton Health Study which involves a series of ongoing health surveys combined with sample collections conducted over four decades in a south-west coastal community of Western Australia (WA) of predominantly Caucasian citizens. [22][23][24][25][26] Here, we present AAb data obtained from this cohort using current National Association of Testing Authorities (NATA) accredited commercial or in house laboratory assays.…”
Section: Introductionmentioning
confidence: 99%